Low-Concentration Oxygen/Ozone Treatment Attenuated Radiculitis and Mechanical Allodynia via PDE2A-cAMP/cGMP-NF-κB/p65 Signaling in Chronic Radiculitis Rats - Junnan Wang; Mingyi Wu; Xiaowen Lin; Yun Li; Zhijian Fu (Pain Research and Management)
Background. Oxygen/ozone therapy is a minimally invasive technique for the treatment of radiculitis from lumbar disc herniation. This study aimed at investigating whether intrathecal administration of low-concentration oxygen/ozone could attenuate chronic radiculitis and mechanical allodynia after noncompressive lumbar disc herniation and at elucidating the underlying mechanisms. Methods. First, we transplanted autologous nucleus pulposus into dorsal root ganglions to establish chronic radiculitis in rats. Then, filtered oxygen or oxygen/ozone (10, 20, or 30 μg/mL) was intrathecally injected on day 1 after surgery. The ipsilateral paw withdrawal thresholds (PWTs) to mechanical stimuli were tested daily with von Frey filaments. The expression of the tumor necrosis factor- (TNF-) α, interleukin- (IL-) 1β, IL-6, cyclic adenosine monophosphate (cAMP), cyclic guanosine monophosphate (cGMP), phosphodiesterase 2A (PDE2A), and nuclear factor- (NF-) κB/p65 in spinal dorsal horns was measured by enzyme-linked immunosorbent assay, polymerase chain reaction, and western blot on day 7 after surgery. Results. Chronic radiculitis was established in rats. Intrathecal administration of 10 μg/mL, 20 μg/mL, or 30 μg/mL oxygen/ozone significantly attenuated the decreased mechanical PWTs, downregulated the overexpression of spinal TNF-α, IL-1β, and IL-6, and increased the expression of cGMP and cAMP in chronic radiculitis rats. In addition, the effects of treatment with 20 μg/mL oxygen/ozone were greater than the effects of the 10 μg/mL or 30 μg/mL doses. Moreover, intrathecal administration of 20 μg/mL oxygen/ozone reversed the increased levels of spinal PDE2A and NF-κB/p65 mRNA and protein expressions in rats with chronic radiculitis. Conclusion. Intrathecal administration of low-concentration oxygen/ozone alleviated mechanical allodynia and attenuated radiculitis, likely by a PDE2A-cGMP/cAMP-NF-κB/p65 signaling pathway in chronic radiculitis rats.